2020
DOI: 10.1186/s12885-020-6658-1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor mutational burden is associated with poor outcomes in diffuse glioma

Abstract: Background: Tumor mutational burden (TMB) is a potential biomarker for immune checkpoint therapy and prognosis. The impact of TMB on clinical outcomes and the correlation coefficient between exome sequencing and targeted sequencing in glioma have not yet been explored. Methods: Somatic mutations in the coding regions of 897 primary gliomas and the clinical and RNA-seq data of 654 patients in The Cancer Genome Atlas (TCGA) database were analyzed as a training set, while another 286 patients in the Chinese Gliom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 25 publications
6
58
0
Order By: Relevance
“…3). Very low TMB is associated with favorable survival in WHO grade III anaplastic astrocytoma, but not in WHO grade IV GBM 9,13 . Indeed, we confirmed no survival differences in immunotherapynaïve primary (n = 277) or rGBM (n = 132) 11 patient cohorts upon stratification by TMB (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…3). Very low TMB is associated with favorable survival in WHO grade III anaplastic astrocytoma, but not in WHO grade IV GBM 9,13 . Indeed, we confirmed no survival differences in immunotherapynaïve primary (n = 277) or rGBM (n = 132) 11 patient cohorts upon stratification by TMB (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Interestingly, the results of the Kaplan–Meier analysis showed that patients in high TMB group had a poorer prognosis, higher tumor grades, and advanced pathological subtypes. A recent bioinformatics study showed that the high tumor proliferative activity in high TMB patients may lead to a shorter OS of glioma, but more experiments are still needed to validate their findings ( 28 ). As high TMB patients usually benefit from immunotherapy ( 17 , 29 ), higher TMB glioma patients may be able to achieve a better prognosis once immunotherapy is widely utilized in the treatment of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…TMB is a promising biomarker, and studies have shown that high TMB is positively correlated with immunotherapy [39]. In addition, TMB is closely related to the overall survival rate and tumor proliferative activity of glioma patients [40]. Therefore, it is an important reference factor in the treatment and prognosis of glioma.…”
Section: Immunohistochemical Resultsmentioning
confidence: 99%